Electrochromic multicolour and multi-state variable tint glass and method of manufacture
Patent Information
- Application Number
- CN202611182529.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]本发明是要解决道桥的遮光顶棚等电致变色场景采用的电致变色玻璃表现出颜色变化少、调控差、能耗高,循环性能差以及低温不耐受等问题,而提供一种基于铜/亚铜电致转换实现电致变色玻璃的无色态-透光茶色态-镜面态-白色蔽光态的多变色方法
1、现有电致变色玻璃中,采用二价铜作为电解质溶液的铜基电致变色玻璃,由于二价铜离子的蓝色而无法实现真正意义的无色态。更为严重的是,铜电化学氧化为二价铜的过程中会产生少量一价铜,导致体系可逆程度降低,构建的电致变色玻璃的光学性能变化也失去稳定性。不仅如此,铜基电致变色玻璃的色态变化较少,只能实现无色态、有色透光态和镜面态之间的转换,并不能够满足道桥遮光顶棚等电致变色场景的光线变化要求。因此,开发出基于金属铜和亚铜化合物之间电化学转换实现导电玻璃多色多态变化的方法意义重大,具有节能、颜色多变、调控简单等优点。
Smart Images

Figure CN122984253A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochromic glass technology, specifically relating to an electrochromic glass with multiple colors and states and its preparation method. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Electrochromism refers to the stable and reversible change in the optical properties (reflectivity, transmittance, absorptivity, etc.) of a device under the influence of an applied electric field. Essentially, it is an electrochemical reaction driving changes in optical performance. Due to its advantages such as precise controllability, low energy consumption, and excellent memory effect, electrochromic glass is used in road and bridge applications, including sunshade canopies and highway guard booths. It can regulate spatial light intensity, comfort, and temperature through color changes and color state transitions.
[0004] Among the many types of electrochromic glasses, those based on reversible metal electrodeposition can electrochemically control and switch between various optical states, including colorless, colored, and specular states. Copper-based electrochromic glasses have a clear advantage among various metal-based electrochromic glasses due to their rich optical properties, low cost, and significant optical changes during reversible redox processes. The transmittance of copper-based electrochromic glasses can be adjusted according to the external environment; when sunlight is strong, applying voltage causes the glass to change its color state, blocking or even reflecting light and heat, while it returns to transparency when light is insufficient, ensuring sufficient light transmission. However, reversible metal electrodeposition electrochromic glasses also have some limitations, such as limited changes in optical state and color, and poor controllability of the electrochromic process. Summary of the Invention
[0005] This invention aims to address the problems of limited color change, poor control, high energy consumption, poor cycle performance, and low-temperature intolerance exhibited by electrochromic glass used in scenarios such as sunshade canopies for roads and bridges. Instead, it provides a method based on copper / copper sub-copper electrochromic conversion to achieve multiple color-changing states of electrochromic glass, including colorless, translucent brown, mirror-like, and white sunshade states.
[0006] To achieve the above-mentioned technical effects, the present invention provides the following technical content: In a first aspect, an electrochromic multicolor glass is provided, the electrochromic glass comprising a conductive glass and a sealing glass arranged in parallel, the two being fixed by a frame to form a sealed cavity, the cavity being filled with an electrochromic solution.
[0007] Furthermore, the conductive glass can be selected from ITO conductive glass or FTO fluorine-doped tin oxide conductive glass. One side of the conductive glass is covered with a conductive film, and the conductive film is inwardly contacted with the electrochromic solution. The conductive film is connected to a first tab, extending beyond the frame for connection to an external DC voltage regulator circuit. Even further, the first tab is made of nickel-plated oxygen-free copper.
[0008] Furthermore, the frame includes a sealing frame and a metal frame arranged side by side; in this embodiment, the conductive glass and the metal frame are like two electrodes of an electrolytic device, both of which should be able to fully contact the electrochromic solution, and the two electrodes should not contact each other; to meet the above structural requirements, the frame is arranged in a side-by-side configuration of a sealing frame-metal frame-sealing frame to clamp the components. The sealing frame is mainly used for sealing, limiting, and insulating; feasible materials include silicone, fluororubber, butyl rubber, polyurethane sealant, and polytetrafluoroethylene. A feasible material for the metal frame is oxygen-free copper; the metal frame has a second tab, which, together with the first tab, is connected to an external DC regulated power supply, and is made of nickel-plated oxygen-free copper.
[0009] Furthermore, the material of the sealing glass can be selected from float glass, borosilicate glass, aluminosilicate glass, or quartz glass.
[0010] In the electrochromic solution provided in the first aspect above, CuCl formed by cuprous chloride and thiourea (TU) The 3TU soluble coordination complex is an electrolyte, dissolved in a deep eutectic solvent. Under the action of DC currents of different magnitudes and polarities, cuprous ions in the system undergo reversible electrodeposition and anodic dissolution reactions on the conductive glass surface: when a cathodic current is applied, cuprous ions gradually deposit on the conductive glass surface, successively forming a fine-grained, uniform, transparent brown copper film, and a larger, flat, reflective mirror copper film. When a large current is applied for anodic oxidation, the cuprous coordination complex is transformed into a poorly soluble CuCl·3TU nanowire film, exhibiting a milky white, completely opaque state. Switching to a small anodic current can dissolve the copper film, restoring it to a colorless, transparent state. Relying on the reversible formation and dissolution of different morphologies of the copper-based film, reversible switching between four optical states—colorless, transparent brown, mirror, and white opaque—is achieved. Verification shows that the above electrochromic solution can still stably achieve the conversion effect after thousands of electrochemical conversions and has good temperature tolerance, meeting the requirements of outdoor working conditions.
[0011] In some embodiments verified by this invention, the deep eutectic solvent is composed of choline chloride and ethylene glycol; further, the molar ratio of choline chloride to ethylene glycol is 1:1 to 3, and even further, it is 1:2.
[0012] In other embodiments with better effects, the electrochromic solution also contains a conductive salt that regulates ionic conductivity and promotes the white light-blocking state, such as potassium chloride (KCl), sodium chloride (NaCl), and lithium chloride (LiCl). In some embodiments verified by the present invention, the conductive salt is potassium chloride, and in this embodiment, the molar ratio of cuprous salt to potassium chloride is 1.5~3:1.
[0013] Secondly, a method for preparing the electrochromic glass described in the first aspect is provided, comprising the following steps: (1) Preparation of cuprous salt: Thiourea is dissolved in organic acid to prepare a thiourea solution with a concentration of 170~180g / L. Cuprous chloride is added according to the molar ratio of thiourea to cuprous chloride 3:1. After the saturated solution is cooled, the precipitated crystals are separated and dried to obtain the cuprous salt. (2) Construction of electrochromic system: Dissolve the cuprous salt and conductive salt in a deep eutectic solvent to obtain an electrochromic solution; inject the electrochromic solution into the cavity between the assembled conductive glass and the sealed glass, and connect a DC power supply to obtain the system.
[0014] In the preparation of cuprous salt, the present invention uses an organic acid with a certain coordination ability to dissolve thiourea in step (1), which maintains an acidic environment and improves the stability of thiourea during dissolution, while also promoting the dissolution of cuprous chloride. When cuprous chloride is added in a molar ratio of 3:1 for thiourea and cuprous chloride, the cuprous chloride can dissolve in the thiourea solution to form a stable complex. When the solution is cooled, the solubility of the complex formed by cuprous ions and thiourea decreases rapidly with decreasing temperature, resulting in a supersaturated state in the solution. When the supersaturation reaches a certain level, crystals, i.e., cuprous salt, will precipitate. When cuprous salt and potassium chloride are dissolved in a deep eutectic solvent, an electrochromic solution is obtained. Since the electrochromic solution does not contain water, the electrochemical reversibility is improved, and the disproportionation reaction of cuprous ions and the side reaction of water electrolysis do not occur, which can greatly improve the cyclic reversibility of the electrochromic process. More importantly, the eutectic solvent prepared from choline chloride and ethylene glycol in a 1:2 ratio has a melting point below -60°C. Therefore, the electrolyte of this invention has strong low-temperature resistance, improving the low-temperature electrochromic capability of the electrochromic system. Furthermore, the large amount of thiourea generated after the dissociation of cuprous salt in the electrochromic solution can increase cathodic polarization, refine the grains of the copper deposition layer, form a smooth and clean copper film, and improve the optical performance of the electrochromic glass. After sequentially stacking and clamping conductive glass and sealing glass and injecting them into the electrochromic solution, an electrochromic system based on the electrochemical reversibility between metallic copper and cuprous compounds can be formed by connecting an external DC regulated power supply. Due to the excellent electrochemical reversibility of the electrochromic system, a lower applied voltage is required during the electrochromic process, saving energy consumption.
[0015] The electrochemical reversibility between metallic copper and cuprous compounds is a single-electron process, and under the same current, it is more efficient than Cu. 2+ The electrochemical process involving Cu involves twice as many substances, resulting in faster electrochromic modulation. Therefore, at normal temperatures, when a colorless conductive glass passes through a current of 1.5 mA / cm², the electrochromic modulation speed is significantly faster. 2 When the cathode current is applied, Cu occurs. + →The Cu0 process, after 20 seconds of electrolysis, yields a thin copper film on the conductive glass surface, transforming it into a translucent, amber-colored state, with an applied voltage of only about 0.2V; when the translucent, amber-colored conductive glass continues to pass through a voltage of 3.0 mA / cm... 2 At a cathode current of approximately 0.3 V, the copper film thickens and transforms into a mirror-like state after 10 seconds of electrolysis. During the anodic process of electrochemical oxidation of metallic copper to cuprous compounds, the reaction rate is relatively slow under low current, resulting in the formation of a soluble cuprous ion complex CuCl·3TU. Under high current, the reaction rate is faster, leading to the precipitation of a large amount of Cu. + A sparingly soluble white CuCl·TU film is formed with the synergistic effect of potassium chloride, and the formed CuCl·TU is stable. At room temperature, when the mirror-state conductive glass passes through a current of 10.0 mA / cm... 2 At a high anodic current (large current), due to the large amount of chloride ions in the solution, metallic copper is oxidized to form a sparingly soluble white CuCl·TU film. This film transforms into a white, opaque state within 6 seconds of electrolysis, requiring only about 0.6 V of applied voltage. When the white, opaque conductive glass passes through a current of 1.0 mA / cm²,... 2 When the cathode current is applied, the sparingly soluble CuCl·TU white film is reduced to reform metallic copper, and after 60 s of electrolysis, it transforms back into a mirror state, with an applied voltage of only about 0.3 V; when the mirror-state conductive glass passes through a current of 1.0 mA / cm², 2 When the anodic current is applied, metallic copper forms soluble cuprous complex ions during the small-current oxidation process, and then transforms back into a colorless state after 60 s of electrolysis, with an applied voltage of only about 0.2 V. Therefore, in the electrochromic process, not only is the control speed fast and the color changes numerous, but the energy consumption is also low. Moreover, the constructed electrochromic system can still effectively achieve electrochromism at temperatures below 0℃, although the applied voltage is slightly higher than at room temperature due to increased polarization.
[0016] In step (1) above, there is also the following preferred solution: Furthermore, the organic acid is selected from one of citric acid, gluconic acid, malic acid, and tartaric acid, and the concentration of the organic acid solution is 20~30g / L.
[0017] Furthermore, before adding thiourea, the organic acid solution is preheated to 80-90°C. After heating the thiourea, the solution is stirred thoroughly and filtered while hot to remove insoluble matter, resulting in a saturated solution. The saturated solution is then placed in a water bath at 0-10°C for 24-36 hours to separate and precipitate crystals.
[0018] In step (2) above, there is also the following preferred solution: The electrochromic solution is prepared as follows: the cuprous salt is dissolved in a deep eutectic solvent to obtain a cuprous salt solution, the conductive salt is also added to the deep eutectic solvent to obtain a conductive salt solution, and the cuprous salt solution and the conductive salt solution are mixed in equal volumes to obtain the final solution.
[0019] In one embodiment verified by this invention, the conductive salt is potassium chloride, and in the electrochromic solution, the concentration of the cuprous salt is 0.1 mol / L, and the concentration of the potassium chloride is 0.15~0.3 mol / L. Further, in this embodiment, the eutectic solvent is prepared by mixing choline chloride and ethylene glycol at a molar ratio of 1:2, and the eutectic solvent should be completely anhydrous. Its preparation method is as follows: Choline chloride that has undergone dehydration treatment and ethylene glycol that has undergone dehydration treatment are mixed at a molar ratio of 1:2, sealed to isolate air, and stirred thoroughly at 60~80°C for 2~4 h.
[0020] The DC power supply is a constant current output power supply, which can switch between negative cathode constant current and positive anode constant current, and can stably output 1.0, 1.5, 3.0, and 10.0 mA / cm². 2 Multiple constant current settings.
[0021] Thirdly, a method for electrochromic glass as described in the first aspect is provided, the method being as follows: When no power is applied, the conductive glass is colorless; 1.5 mA / cm 2 When the cathode current is applied, after 20 seconds of electrolysis, the conductive glass changes from a colorless state to a transparent brown state. 3.0 mA / cm 2 After 10 seconds of cathode current electrolysis, the conductive glass changes from a translucent brown state to a mirror state. 10.0 mA / cm 2 After 6 seconds of electrolysis with the anodic current, the conductive glass changes from a mirror state to a white, light-shielding state. 1.0 mA / cm 2 After 60 seconds of cathodic electrolysis, the conductive glass changes from a white, light-shielding state to a mirror-like state. 1.0 mA / cm 2 After electrolysis with the anodic current for 60 seconds, the conductive glass changes from a mirror state to a colorless state.
[0022] Compared with the prior art, the beneficial effects of the present invention are: 1. In existing electrochromic glasses, copper-based electrochromic glasses using divalent copper as the electrolyte solution cannot achieve a truly colorless state due to the blue color of divalent copper ions. More seriously, the electrochemical oxidation of copper to divalent copper produces a small amount of monovalent copper, reducing the system's reversibility and causing instability in the optical properties of the constructed electrochromic glass. Furthermore, copper-based electrochromic glasses offer limited color state changes, only achieving transitions between colorless, colored transparent, and specular states, which cannot meet the light variation requirements of electrochromic scenarios such as bridge and road shading canopies. Therefore, developing a method for achieving multi-color and multi-state changes in conductive glass based on the electrochemical conversion between metallic copper and cuprous compounds is of great significance, offering advantages such as energy saving, multiple color variations, and simple control.
[0023] 2. The cuprous salt prepared by this invention can be stably dissolved in a deep eutectic solvent with potassium chloride. The electrochromic system constructed using a colorless cuprous salt not only improves the transmittance of the colorless state, but also facilitates rapid electrochromic transformation through a single-electron process. Furthermore, the deep eutectic solvent significantly enhances the cycling performance and low-temperature resistance of the electrochromic process, meeting outdoor operating conditions, enabling long-term service, and reducing maintenance and replacement costs. Moreover, the method for controlling the colorless, translucent brown, specular, and white opaque states of conductive glass is simple and offers diverse color variations, making it suitable for electrochromic applications in wide-temperature environments such as shading canopies for roads and bridges. Attached Figure Description
[0024] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0025] Figure 1 This is a schematic diagram of the structure of the electrochromic glass described in this invention; Figure 2 This is a side view of the electrochromic glass described in Example 1; Figure 3 This is an exploded view of the electrochromic glass described in Example 2; The above Figures 1-3 In the diagram, 1 is conductive glass, 2 is a copper frame, 3 is sealing glass, 4 is a silicone frame, 101 is a first electrode tab, and 102 is a second electrode tab. Figure 4 These are images of the appearance of the conductive glass in Example 2 at room temperature in the following states: colorless, translucent brown, mirror-like, and white opaque states. in, Figure 4 A is a colorless conductive glass; Figure 4 Type B is a translucent, brownish-red conductive glass; Figure 4 C in the middle represents mirror-finish conductive glass; Figure 4 D in the middle is a white, light-shielding conductive glass; Figure 5 The images shown are scanning electron microscope images of conductive glass at room temperature in the following states: transparent brown, mirror, and white opaque states, as described in Example 2. Figure 6 The images show the appearance of the conductive glass in Example 8 at -10°C in colorless, translucent brown, mirror-like, and white opaque states. in, Figure 6 A is a colorless conductive glass; Figure 6 Type B is a translucent, brownish-red conductive glass; Figure 6 C in the middle represents mirror-finish conductive glass; Figure 6 D in the middle is a white, light-shielding conductive glass; Figure 7 The image shows scanning electron micrographs of conductive glass at -10°C in its transparent brown, mirror, and white opaque states, as described in Example 8. Detailed Implementation
[0026] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0027] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0028] In the context of this invention, the word "comprising" is considered to mean "particularly including". It should not be interpreted as "consisting of only".
[0029] In the description of this invention, it should be understood that the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. The symbol " / " in this document indicates that the related objects are in an "or" relationship; for example, A / B means A or B.
[0030] In the description of embodiments of the present invention, the words "exemplary" or "for example" are used to indicate that they are examples, illustrations, or descriptions. Any embodiment or design that is described as "exemplary" or "for example" in the embodiments of the present invention should not be construed as being more preferred or advantageous than other embodiments or design. Specifically, the use of the words "exemplary" or "for example" is intended to present the relevant concepts in a specific manner.
[0031] In the description of the embodiments of the present invention, unless otherwise stated, "a plurality of" means two or more.
[0032] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0033] Example 1 In this embodiment, an electrochromic glass with multiple colors and states is provided, the structure of which is as follows: Figure 1 As shown in the diagram, it includes a conductive glass 1 and a sealing glass 3 arranged in parallel. The two are fixed by a frame and form a cavity, which is filled with an electrochromic solution.
[0034] The conductive glass 1 is made of ITO glass material and has a size of 5cm×5cm. One side of the conductive film is in contact with the electrochromic solution, and the other side of the conductive film also has a first tab 101 that extends outward.
[0035] The sealing glass 3 is made of quartz glass and has the same dimensions as the conductive glass 1.
[0036] The frame includes a silicone frame 4 and a copper frame 2 arranged side by side, positioned between the two glass plates in a silicone frame-copper frame-silicone frame configuration (e.g., ...). Figure 2 The silicone frame 4 is used to encapsulate the glass plate and provide insulation. The copper frame 4 has a second tab 102 on its side, which, together with the first tab 101, is connected to an external DC regulated power supply.
[0037] The electrochromic solution is a deep eutectic solvent system for dispersing cuprous salt.
[0038] Example 2 In this embodiment, a method for preparing the electrochromic glass described in Example 1 is provided, comprising the following steps: (1) Preparation of cuprous salt: Thiourea was dissolved in citric acid solution (30 g / L) at 80℃ to prepare a thiourea concentration of 170 g / L. Then, cuprous chloride was added at a molar ratio of 3:1 between thiourea and cuprous chloride. The mixture was stirred at 80℃ and the insoluble matter was filtered off while hot. The filtered solution was cooled to room temperature by air and then placed in a constant temperature water bath at 10℃ for 36 h to precipitate block crystals. The precipitated block crystals were taken out and freeze-dried to obtain cuprous salt, which is the soluble coordination complex formed by cuprous chloride and thiourea.
[0039] (2) Construction of electrochromic system: Dissolve the cuprous salt prepared in step (1) in a deep eutectic solvent to prepare a 0.2 mol / L cuprous salt solution. Then dissolve the dehydrated potassium chloride in a deep eutectic solvent to prepare a 0.5 mol / L potassium chloride solution. Slowly add the solution to an equal volume of cuprous salt solution and stir until homogeneous to obtain an electrochromic solution (0.25 mol / L potassium chloride + 0.1 mol / L cuprous salt).
[0040] according to Figure 3 The conductive glass 1, sealing glass 3, silicone frame 4 and copper frame 2 are assembled as shown. The electrochromic solution is injected into the cavity between the assembled conductive glass 1 and sealing glass 3. After isolating the air, an external DC regulated power supply is connected through the first tab 101 and the second tab 102 to form an electrochromic system.
[0041] The above-mentioned deep eutectic solvent is prepared by mixing dehydrated choline chloride and dehydrated ethylene glycol at a molar ratio of 1:2, sealing and isolating from air, and then stirring thoroughly at 70°C for 3 hours.
[0042] The method for changing the color of the electrochromic glass by applying an electrical signal is as follows: At 25°C without power, the conductive glass is colorless. 1.5 mA / cm 2 After electrolysis for 20 seconds at a cathode current of 0.18 V, the conductive glass changes from a colorless state to a transparent brown state. 3.0 mA / cm 2 After 10 seconds of cathode current electrolysis, the conductive glass changes from a translucent brown state to a mirror state, at which point the applied voltage is only 0.29V. 10.0 mA / cm 2 After 6 seconds of electrolysis with the anodic current, the conductive glass changes from a mirror state to a white, light-shielding state, at which point the applied voltage is only 0.59V. 1.0 mA / cm 2 After 60 seconds of cathodic electrolysis, the conductive glass changes from a white, light-blocking state to a mirror-like state, at which point the applied voltage is only 0.32V. 1.0 mA / cm 2 After 60 seconds of electrolysis with the anodic current, the conductive glass changes from a mirror state to a colorless state, at which point the applied voltage is only 0.21 V.
[0043] In this embodiment, X-ray single-crystal diffraction analysis was performed on the crystal structure of the cuprous salt obtained in step (1) above to determine that the cuprous salt is a single-component crystal with the molecular formula CuCl·3TU. The bond angles obtained by X-ray single-crystal diffraction analysis are shown in Table 1.
[0044] Table 1. Bond angle analysis results of X-ray single-crystal diffraction of cuprous salts. Images of the appearance of conductive glass at room temperature in colorless, translucent brown, mirror-like, and white opaque states are shown below. Figure 4 As shown, a piece of paper printed with "green" is placed behind conductive glass. (By...) Figure 4 It can be seen that: the colorless state of conductive glass does not have the traditional blue-green interference of divalent copper ions; the translucent brown state of conductive glass is a translucent brown color; the mirror state of conductive glass is a completely opaque state, resembling a copper mirror with excellent reflectivity; and the white opaque state of conductive glass is a completely opaque milky white state. Scanning electron micrographs of conductive glass in the translucent brown, mirror, and white opaque states at room temperature are shown below. Figure 5 As shown. By Figure 5 It can be seen that: the translucent brown copper film is uniform and has very fine grains; the mirror-like copper film has larger grains, but the surface is still flat, which is beneficial for optical reflection; the white opaque state is actually a thin film composed of insoluble CuCl·3TU nanowires, and the film layer is uniform.
[0045] Example 3 In this embodiment, another method for preparing electrochromic glass is provided, comprising the following steps: (1) Preparation of cuprous salt: Thiourea was dissolved in a gluconic acid solution (20 g / L) at 90°C to prepare a thiourea concentration of 170 g / L. Then, cuprous chloride was added at a molar ratio of 2:1 between thiourea and cuprous chloride. The mixture was stirred at 90°C and the insoluble matter was filtered off while hot. The filtered solution was cooled to room temperature by air and then placed in a constant temperature water bath at 10°C for 24 h to precipitate blocky crystals. The precipitated blocky crystals were taken out and freeze-dried to obtain cuprous salt, which is the soluble coordination complex formed by cuprous chloride and thiourea.
[0046] (2) Construction of electrochromic system: The cuprous salt prepared in step (1) was dissolved in a eutectic solvent (choline chloride-ethylene glycol, molar ratio 1:2) to prepare a 0.2 mol / L cuprous salt solution. Then, the dehydrated potassium chloride was dissolved in a eutectic solvent to prepare a 0.3 mol / L potassium chloride solution. The solution was then slowly added to an equal volume of cuprous salt solution and stirred until homogeneous to obtain an electrochromic solution (0.15 mol / L potassium chloride + 0.1 mol / L cuprous salt).
[0047] The electrochromic glass was assembled according to the method in Example 2.
[0048] Example 4 In this embodiment, another method for preparing electrochromic glass is provided, comprising the following steps: (1) Preparation of cuprous salt: Thiourea was dissolved in malic acid solution (25 g / L) at 85℃ to prepare a thiourea concentration of 175 g / L. Then, cuprous chloride was added at a molar ratio of 4:1 between thiourea and cuprous chloride. The mixture was stirred at 85℃ and the insoluble matter was filtered off while hot. The filtered solution was cooled to room temperature by air and then placed in a constant temperature water bath at 10℃ for 30 hours to precipitate block crystals. The precipitated block crystals were taken out and freeze-dried to obtain cuprous salt, which is the soluble coordination complex formed by cuprous chloride and thiourea.
[0049] (2) Construction of electrochromic system: The cuprous salt prepared in step (1) was dissolved in a eutectic solvent (choline chloride-ethylene glycol, molar ratio 1:2) to prepare a 0.2 mol / L cuprous salt solution. Then, the dehydrated potassium chloride was dissolved in a eutectic solvent to prepare a 0.6 mol / L potassium chloride solution. The solution was then slowly added to an equal volume of cuprous salt solution and stirred until homogeneous to obtain an electrochromic solution (0.3 mol / L potassium chloride + 0.1 mol / L cuprous salt).
[0050] The electrochromic glass was assembled according to the method in Example 2.
[0051] The method for changing the color of the above-mentioned conductive glass by applying an electrical signal is as follows: At 25°C without power, the conductive glass is colorless. 1.5 mA / cm 2 After electrolysis for 20 seconds at a cathode current of 0.19V, the conductive glass changes from a colorless state to a transparent brown state. 3.0 mA / cm 2 After 10 seconds of cathode current electrolysis, the conductive glass changes from a translucent brown state to a mirror state, at which point the applied voltage is only 0.33V. 10.0 mA / cm 2After 6 seconds of electrolysis with the anodic current, the conductive glass changes from a mirror state to a white, light-shielding state, at which point the applied voltage is only 0.65V. 1.0 mA / cm 2 After 60 seconds of cathodic electrolysis, the conductive glass changes from a white, light-shielding state to a mirror state, at which point the applied voltage is only 0.35V. 1.0 mA / cm 2 After 60 seconds of electrolysis with the anodic current, the conductive glass changes from a mirror state to a colorless state, at which point the applied voltage is only 0.25V.
[0052] Example 5 In this embodiment, another method for preparing electrochromic glass is provided. The difference from Example 2 is that in step (1), thiourea is dissolved in tartaric acid solution (30 g / L) at 80°C to prepare an organic acid solution of thiourea.
[0053] Example 6 In this embodiment, another method for preparing electrochromic glass is provided. The difference from Example 2 is that in step (2), the concentration of potassium chloride solution is 0.5 mol / L.
[0054] Example 7 In this embodiment, another method for preparing electrochromic glass is provided. The difference from Example 2 is that, in step (2), the preparation method of the deep eutectic solvent is as follows: The mixture was prepared by mixing dehydrated choline chloride and dehydrated ethylene glycol at a molar ratio of 1:2, sealing it to isolate it from air, and stirring it thoroughly at 60°C for 2 hours.
[0055] Example 8 In this embodiment, an electrical signal is applied to the conductive glass described in Example 2 at -10°C to perform a color-changing operation: When no power is applied, the conductive glass is colorless; 1.5 mA / cm 2 After electrolysis for 20 seconds at the cathode current, the conductive glass changes from a colorless state to a transparent brown state, at which point the applied voltage is only 0.51V. 3.0 mA / cm 2 After 10 seconds of cathode current electrolysis, the conductive glass changes from a translucent brown state to a mirror state, at which point the applied voltage is only 0.86V. 10.0 mA / cm 2 After 6 seconds of electrolysis with the anodic current, the conductive glass changes from a mirror state to a white, light-shielding state, at which point the applied voltage is only 1.52V. 1.0 mA / cm 2After 60 seconds of cathodic electrolysis, the conductive glass changes from a white, light-shielding state to a mirror state, at which point the applied voltage is only 0.91V. 1.0 mA / cm 2 After 60 seconds of electrolysis with the anodic current, the conductive glass changes from a mirror state to a colorless state, at which point the applied voltage is 0.59V.
[0056] Images of the conductive glass in its colorless, translucent brown, specular, and white opaque states are shown below. Figure 6 As shown, paper printed with "Jinan U" was placed behind the conductive glass, and paper printed with "copper plated" was placed in front of the mirror state. It can be seen that significant optical properties are still present in each state; scanning electron micrographs of the conductive glass in the transparent brown state, mirror state, and white opaque state are shown below. Figure 7 As shown, compared to Example 1, only the morphology and size of the copper grains changed in the mirror state; other aspects remained largely unchanged. (Combined with...) Figure 6 and Figure 7 It can be seen that although the applied voltage during the electrochromic process of conductive glass at -10℃ is higher than that at room temperature, the difference in its optical performance and microstructure changes is small. This indicates that the electrochromic system has excellent electrochromic performance at low temperatures, which meets the needs of wide-temperature scenarios such as shading canopies for roads and bridges.
[0057] According to the results of Example 7, the conductive glass can still achieve stable electrochromism at low temperatures. The current conditions and electrolysis time required for color change remain unchanged, only the voltage increases compared to room temperature. This indicates that the conductive glass can stably achieve electrochromism even at low temperatures.
[0058] Example 9 In this embodiment, an electrical signal is applied to the conductive glass described in Example 2 at -18°C to perform a color-changing operation.
[0059] Example 10 In this embodiment, an electrical signal is applied to the conductive glass described in Example 2 at 50°C to perform a color-changing operation.
[0060] The electrochromic system constructed in Examples 2-10 was electrochromically controlled to achieve a cyclic color change from colorless state to translucent brown state to mirror state to white opaque state to mirror state and back to colorless state. The changes in optical performance after 1000 cycles are shown in Table 2. It can be seen that there are no significant changes in transmittance, reflectance, etc. in different states after cycling. This indicates that the electrochromic glass based on copper / copper sub-conversion can not only achieve rapid electrochromic changes with low control voltage, but also has a simple method for controlling color and excellent cycle performance. It has a wide range of applications and meets the needs of high-requirement, wide-temperature electrochromic scenarios such as shading canopies for roads and bridges.
[0061] Table 2. Changes in optical properties of conductive glass in Examples 2-10 before and after 1000 cycles. As shown in Table 2, the transmittance of the aforementioned conductive glass remained within 4% after 1000 cycles. The maximum decrease in transmittance was 3% for the colorless state, 2% for the brown state, 4% for the specular reflectance, and 3% for the white opaque state. Overall, the optical performance degradation was minimal. This indicates that the copper / cuprous electrochromic system of this invention exhibits strong electrochemical reversibility, with no significant decomposition of active materials, film peeling, or ion migration failure during cycling, demonstrating long-term service stability.
[0062] The fact that the light transmittance changes significantly under high temperature, low temperature and normal temperature conditions proves that the electrochromic glass also has excellent temperature resistance and can meet the actual use requirements of outdoor wide temperature and long service life scenarios such as bridge and road shading canopies and building smart dimming glass.
[0063] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. An electrochromic glass with multiple colors and states, characterized in that, The photochromic glass includes a conductive glass and a sealing glass arranged in parallel. The two are fixed by a frame to form a sealed cavity, which is filled with an electrochromic solution.
2. The electrochromic glass with multiple color states as described in claim 1, characterized in that, The conductive glass is selected from ITO conductive glass and FTO fluorine-doped tin oxide conductive glass. One side of the conductive glass is covered with a conductive film, and the conductive film side is in contact with the electrochromic solution. The conductive film is connected to the first tab, extends out of the frame, and is used for external DC voltage regulation circuit. Furthermore, the first electrode is made of nickel-plated oxygen-free copper.
3. The electrochromic glass with multiple color states as described in claim 2, characterized in that, The frame includes a sealing frame and a metal frame arranged side by side; The frame is arranged in a parallel manner of sealing frame-metal frame-sealing frame to clamp the conductive glass and sealing glass; The sealing frame is mainly used for sealing, limiting, and insulating. The material is selected from silicone, fluororubber, butyl rubber, polyurethane sealant, and polytetrafluoroethylene. The metal frame is made of oxygen-free copper. The metal frame has a second tab, which, together with the first tab, is connected to an external DC regulated power supply. The second tab is made of nickel-plated oxygen-free copper.
4. The electrochromic glass with multiple color states as described in claim 1, characterized in that, The sealing glass is made of float glass, borosilicate glass, aluminosilicate glass, or quartz glass.
5. The electrochromic glass with multiple color states as described in claim 1, characterized in that, In the electrochromic solution, CuCl is formed by cuprous chloride and thiourea. The 3TU soluble coordination complex is an electrolyte that dissolves in a deep eutectic solvent; the deep eutectic solvent is composed of choline chloride and ethylene glycol; further, the molar ratio of choline chloride to ethylene glycol is 1:1 to 3, and even further, it is 1:
2.
6. The electrochromic glass with multiple color states as described in claim 1, characterized in that, The electrochromic solution also contains a conductive salt that regulates ionic conductivity and promotes the white light-blocking state. The conductive salt is, but is not limited to, one of potassium chloride, sodium chloride, and lithium chloride. Furthermore, the conductive salt is potassium chloride, and the molar ratio of the cuprous salt to potassium chloride is 1.5~3:
1.
7. A method for preparing the electrochromic glass with multiple color states according to any one of claims 1-6, characterized in that, Includes the following steps: (1) Preparation of cuprous salt: Thiourea is dissolved in organic acid to prepare a thiourea solution with a concentration of 170~180g / L. Cuprous chloride is added according to the molar ratio of thiourea to cuprous chloride 3:
1. After the saturated solution is cooled, the precipitated crystals are separated and dried to obtain the cuprous salt. (2) Construction of electrochromic system: Dissolve the cuprous salt and conductive salt in a deep eutectic solvent to obtain an electrochromic solution; inject the electrochromic solution into the cavity between the assembled conductive glass and the sealed glass, and connect a DC power supply to obtain the system.
8. The method for preparing the electrochromic glass with multiple colors and states as described in claim 7, characterized in that, In step (1), the organic acid is selected from one of citric acid, gluconic acid, malic acid, and tartaric acid, and the concentration of the organic acid solution is 20~30g / L; Before adding thiourea, the organic acid solution is preheated to 80-90°C. After heating the thiourea, the solution is stirred thoroughly and filtered while hot to remove insoluble matter, resulting in a saturated solution. The saturated solution is then placed in a water bath at 0-10°C for 24-36 hours to separate and precipitate crystals.
9. The method for preparing the electrochromic glass with multiple colors and states according to claim 7, characterized in that, In step (2), the electrochromic solution is prepared as follows: the cuprous salt is dissolved in a deep eutectic solvent to obtain a cuprous salt solution, the conductive salt is also added to the deep eutectic solvent to obtain a conductive salt solution, and the cuprous salt solution and the conductive salt solution are mixed in equal volumes to obtain the solution. Further, the conductive salt is potassium chloride, and in the electrochromic solution, the concentration of the cuprous salt is 0.1 mol / L, and the concentration of the potassium chloride is 0.15~0.3 mol / L; Furthermore, the deep eutectic solvent is prepared by mixing choline chloride and ethylene glycol in a molar ratio of 1:2, and the deep eutectic solvent is completely anhydrous. The preparation method is as follows: choline chloride that has been dehydrated and ethylene glycol that have been dehydrated are mixed in a molar ratio of 1:2, sealed to isolate air, and stirred thoroughly at 60~80℃ for 2~4 h. Furthermore, the DC power supply is a constant current output power supply, which can switch between negative cathode constant current and positive anode constant current, and can stably output 1.0, 1.5, 3.0, and 10.0 mA / cm². 2 Multiple constant current settings.
10. The electrochromic method for the electrochromic glass with electrochromic polychromatic states according to any one of claims 1-6, characterized in that, The method is as follows: When no power is applied, the conductive glass is colorless; 1.5 mA / cm 2 When the cathode current is applied, after 20 seconds of electrolysis, the conductive glass changes from a colorless state to a transparent brown state. 3.0 mA / cm 2 After 10 seconds of cathode current electrolysis, the conductive glass changes from a translucent brown state to a mirror state. 10.0 mA / cm 2 After 6 seconds of electrolysis with the anodic current, the conductive glass changes from a mirror state to a white, light-shielding state. 1.0 mA / cm 2 After 60 seconds of cathodic electrolysis, the conductive glass changes from a white, light-shielding state to a mirror-like state. 1.0 mA / cm 2 After electrolysis with the anodic current for 60 seconds, the conductive glass changes from a mirror state to a colorless state.